Atrioventricular Left Ventricular Apical Pacing Improves Haemodynamic, Rotational, and Deformation Variables in Comparison to Pacing at the Lateral Wall in Intact Myocardium: Experimental Study - Savvas Toumanidis; Anna Kaladaridou; Dimitrios Bramos; Elias Skaltsiotes; John Agrios; Constantinos Pamboucas; George Kottis; Anna Antoniou; Elektra Papadopoulou; Spyridon Moulopoulos (Cardiology Research and Practice)
Aim. To assess the effect on left ventricular (LV) function of atrioventricular (AV) and ventricular pacing at the LV apical or lateral wall and to compare the normal torsional and deformation pattern of the intact LV myocardium with those created by the aforementioned LV pacing modes and sites. Methods. Experiments were conducted in pigs (n=21) with normal LV function to investigate the acute hemodynamic effects of epicardial AV and ventricular LV pacing at the LV apical or lateral wall. Torsional and deformation indices of LV function were assessed using speckle tracking echocardiography. Results. AV pacing at the apex revealed a significant reduction in the radial strain of the base (P<0.03), without affecting significantly the ejection fraction and the LV torsion or twist. In contrast, AV pacing at the lateral wall produced, in addition to the reduction of the radial strain of the base (P<0.01), significant reduction of the circumferential and the radial strain of the apex (both P<0.01) as well as of the ejection fraction (P<0.002) and twist (P<0.05). Conclusions. In pig hearts with intact myocardium, LV function is maintained at sinus rhythm level when AV pacing is performed at the LV apex.